Altering the distribution of Pd nano particles on ferroelectric substrate: Dissipative particle dynamics simulation. Issue 4 (2nd November 2018) - Liu, Yue; Tang, Jiaxi; Hua, Chengzhi; Li, Jiuyang; Fu, Kai; Zhu, Haonan
Abstract: Pd nano particles have been widely used as catalyst in chemical industry. However, the catalytic efficiency has been limited by the Aggregation of the Pd. In this paper, the surface aggregation dynamics of Pd on different ferroelectric polarization surface and temperature were reported. Meanwhile, reducing the particle size to obtain the dispersed morphology of Pd was discussed by the dissipative particle dynamics method and density functional theory. The negatively poled surface offered dispersed Pd morphology, the temperature influence will be discussed in the simulation.